Issues of Advocacy and Community Life for African Americans in Ventura County: Report on a survey and interview research partnership between the Community Advocacy Coalition and CSUCI Sociology Capstone Students, December 2020 Report - Alamillo, Jordan; Bay, Niles; Cancino, Daniel; Chavez, Jessica; Fabian, Paola; Felix, Mayra; Garcia, Angel; Guzman, Jesse; Mendez, Dimitri; Mendez, Jesse; et al. (CBR@CSUCI: An annual volume of community-based research, 2025)
EXECUTIVE SUMMARY Project Background: The research project represents a partnership in which Sociology capstone students worked with and on behalf of the Community Advocacy Coalition, an African American advocacy organization in Ventura County, to address questions of interest to them. Methods: The research comprises two components: 1) a survey focused on issues related to quality of life for African Americans in the county, and 2) a series of micro-interviews with community leaders focused on experiences with law enforcement and with microaggressions. Survey / Findings: • Sixty responses were received from 550 surveys distributed. Seventy percent of respondents were residents of Oxnard or Port Hueneme; sixty-four percent were African American. • Respondents indicated that they recognized a number of community issues as relevant and important for African Americans in the county; the most important were Social Justice, Racism, and collaboration with other marginalized communities. • The dominant responses to an open-ended question about concerns in the community produced the following themes: Race relations, Health and environment, and Socio-economic issues. • Respondents indicated that the most important thing that the African American community can do to make Ventura County a better place to live was greater engagement in the community and community events. • A question about possible engagement with the CAC indicated significant interest, with 28% indicating that they would be interested in participating in CAC activities, and another 57% indicated that they may be interested. Interviews / Findings: • Brief interviews were conducted with African American community leaders identified by the CAC. Forty individuals were contacted; thirteen agreed to participate in the interview. • Regarding interactions with law enforcement, the majority reported primarily negative interactions. When asked if they would hesitate to call law enforcement for help, responses were mixed, with about half indicating that they would have some hesitation. • Two general themes emerged from suggestions about ways to reform law enforcement: the need for more cultural sensitivity training, and the need for greater community involvement on the part of law enforcement. • Microaggressions emerged as a common experience among respondents. The context of those experiences were: public interactions, workplace, shopping, or traffic stops. • Several themes emerged regarding changes necessary to improve African American lives in the county: increased political and community involvement; achievement of greater workplace equity; diversifying school curricula; and increased cultural activities/events. Recommendations: The research provides a rich sense of the challenges facing African Americans in Ventura County. A key suggestion for improvement was the need for increased community engagement of all sorts. There was also significant interest among respondents in engaging with the CAC – a resource of which they should take advantage.